Association of Serum Uric Acid Level With Blood Pressure Variability in Newly Diagnosed Essential Hypertension. Issue 12 (7th August 2015) - Çağlı, Kumral; Turak, Osman; Canpolat, Uğur; Özcan, Fırat; Tok, Derya; Mendi, Mehmet Ali; Öksüz, Fatih; Siriopol, Dimitrie; Veisa, Gabriel; Covic, Adrian; Kanbay, Mehmet
Abstract : Serum uric acid (UA) is independently associated with hypertension and blood pressure (BP) variability (BPV) is associated with cardiovascular events and mortality in hypertensive patients. The aim of the present study was to assess the association of serum UA with BPV in 300 untreated essential hypertension patients (mean age 57.3±13.6 years). BPV was quantified as the standard deviation (SD) of the 24‐hour, daytime, and nighttime mean values obtained by using ambulatory BP monitoring. In correlation analysis, log UA values were found to be positively correlated with 24‐hour systolic BPV and nighttime systolic and diastolic BPV (Pearson coefficients of 0.246, 0.280, and 0.353, respectively; P <.001 for all). In multivariate analysis, log UA had an independent association with 24‐hour systolic BPV and nighttime systolic and diastolic BPV. This study show for the first time that increased serum UA is independently associated with BPV in untreated essential hypertension patients.